Ecosystem experiments - Mooney, Harold A.; Medina, Ernesto; Schindler, David W.; Schulze, Ernst-Detlef; Walker, Brian H. (Chichester John Willey & Sons, 1991)
SCOPE report:45
Keywords: Ecology; Nature